2016
DOI: 10.3201/eid2211.160247
|View full text |Cite
|
Sign up to set email alerts
|

Changing Pattern ofChlamydia trachomatisStrains in Lymphogranuloma Venereum Outbreak, France, 2010–2015

Abstract: We describe a change in the molecular epidemiology of Chlamydia trachomatis strains involved in an outbreak of rectal lymphogranuloma venereum in France during January 2010-April 2015. Until 2012, the C. trachomatis L2b strain predominated; however, starting in 2013, most cases involved the L2 strain. We also identified 4 genetic L2b ompA variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
(13 reference statements)
12
32
0
1
Order By: Relevance
“…In accordance with a previous study,23 we found that the L2b ompA variant was not the most common in the pooled data set5 24; the L2 ompA sequence predominated. However, this varied by country as the L2 ompA sequence predominated in Austria, while the L2b omp A sequence predominated in the UK.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with a previous study,23 we found that the L2b ompA variant was not the most common in the pooled data set5 24; the L2 ompA sequence predominated. However, this varied by country as the L2 ompA sequence predominated in Austria, while the L2b omp A sequence predominated in the UK.…”
Section: Discussionsupporting
confidence: 93%
“…However, this varied by country as the L2 ompA sequence predominated in Austria, while the L2b omp A sequence predominated in the UK. We also observed more ompA sequence diversity23 25 than previously reported 5 24. This diversity may be due to more mixed infections and subsequent recombination, sampling from different MSM sexual networks, or the occurrence of single nucleotide polymorphisms through mutations over time.…”
Section: Discussionsupporting
confidence: 41%
“…Thus, the change in testing policy may not be the sole explanation. A hypothetical explanation could be a change in circulating LGV strains over time, as observed in France where the predominating strain changed from L2b to L2 between 2010 and 2015 [23]. Although not supported by French data, less severe clinical features or no symptoms have been observed among patients infected with the L2 strain compared with patients infected with the L2b strain in Spain [24].…”
Section: Discussionmentioning
confidence: 92%
“…These were designated L2bV1 according to a recent article [15]. The sequencing of one isolate failed in spite of repeated attempts because of low copy number of DNA.…”
Section: Resultsmentioning
confidence: 99%